Seroprevalence of Cytomegalovirus among Blood Donor in Transfusion Medicine: Study from Bangladesh - Islam Shaheen, Dr. Sheikh Saiful; Hoque, Dr. Md. Ashraful; Ferdous, Dr. Jannatul (International Journal of Innovative Research in Medical Science, 2020)
Background: Cytomegalovirus (CMV) infection is a matter for concern among blood bank professionals and blood transfusion recipient, especially in cases of transfusion to neonates and immunocompromised patients. Objective: The aim of the study was to investigate the seroprevalence of cytomegalovirus with the purpose of determining routine CMV screening for donors. Method: A descriptive cross sectional study was carried out in the Department of Transfusion Medicine in Bangabandhu Sheikh Mujib Medical University from January 2017 to December 2017. A total of 150 blood donors were selected by convenient sampling technique. Result: The seroprevalence of cytomegalovirus is 91% for IgG and 4% for IgM. Association was found in between IgG and age,sex.In case of age anti-CMV-IgG,c2= 26.5, t = 9.49; c2> t (Association Exists),for sex anti-CMV-IgG: df = 1, CI = 95%, c2= 17.8, t = 3.84; c2> t (Association Exists)Anti-CMV-IgM: df = 1, CI = 95%, c2= 10.7, t = 3.84; c2> t (Association Exist). This study was undertaken to find out seroprevalence of Cytomegalovirus among blood donors in the department of transfusion medicine. The incidence of cytomegalovirus is 91.3% for IgG and 4% for IgM. Most of the IgG positive subjects were in 38-47 years and for IgM were in 28-37 years. It was observed that seroprevalence of CMV was more in female (94.9% in case of IgG& 6.8% in IgM). It was observed that the highest prevalence of IgG was 3out of 3 (100%)in illiterate and that of IgM was 1 out of 3(33.33%) in illiterate level of education. In conclusion it was found that seroprevalence of cytomegalovirus was 91.3% for IgG and 4% for IgM. Association was found in between IgG & age, sex. Conclusion: Prospective blood donors should be screened for CMV most especially for immunocompromised recipients. Leucoreduced blood products from CMV seronegative donors should be given to preterm neonates, infants as this will prevent transfusion associated perinatal CMV disease. There should be more campaign and awareness on provision of voluntary blood donation for CMV negative blood. Program should be made to create awareness in the community on the significant impact of CMV infection on health.